A Novel Approach to High‐Performance Aliovalent‐Substituted Catalysts—2D Bimetallic MOF‐Derived CeCuOx Microsheets. Issue 42 (25th August 2019) - Wang, Qingyue; Li, Zhimin; Bañares, Miguel A.; Weng, Lu‐Tao; Gu, Qinfen; Price, Jason; Han, Wei; Yeung, King Lun
Abstract: Mixed transition metal oxides (MTMOs) have enormous potential applications in energy and environment. Their use as catalysts for the treatment of environmental pollution requires further enhancement in activity and stability. This work presents a new synthesis approach that is both convenient and effective in preparing binary metal oxide catalysts (CeCuO x ) with excellent activity by achieving molecular‐level mixing to promote aliovalent substitution. It also allows a single, pure MTMO to be prepared for enhanced stability under reaction by using a bimetallic metal–organic framework (MOF) as the catalyst precursor. This approach also enables the direct manipulation of the shape and form of the MTMO catalyst by controlling the crystallization and growth of the MOF precursor. A 2D CeCuO x catalyst is investigated for the oxidation reactions of methanol, acetone, toluene, and o ‐xylene. The catalyst can catalyze the complete reactions of these molecules into CO2 at temperatures below 200 °C, representing a significant improvement in performance. Furthermore, the catalyst can tolerate high moisture content without deactivation. Abstract : A mixed transition metal oxide catalyst is prepared via the thermal transformation of a bimetallic metal–organic framework precursor. The as‐synthesized CeCuO x catalyst exhibits unique properties with high aliovalent substitution, abundant oxygen vacancies, and exposed active crystal planes, leading to high reactivity and moisture tolerance for the complete oxidation of various volatile organic compounds (i.e., toluene, o ‐xylene, acetone, and methanol).